Literasi Digital Sebagai Upaya Kritis Memerangi Berita Bohong: Studi Terhadap Gerakan Masyarakat Anti Fitnah Indonesia (MAFINDO) - Rintis Mulyaning Ati; Albertus Rhangga; Puti Anggraini (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
The digitalization of the internet in all aspects of people's lives is part of the results of civilization, which should be used by society to form civilized activities as well. But in fact, the internet, which is believed to be able to positively facilitate all community activities, actually has a negative impact. This study aims to find out how the concept of symbolic interactionism is processed in fact checking by. MAFINDO. This study uses the Symbolic Interactionism Theory paradigm and applies a descriptive qualitative method by looking at the mafindo case on social media. This study used in-depth interviews at the MAFINDO Presidium as the object of research. The results of this study indicate that Instagram social media has become a new public space forum, MAFINDO utilizes its Instagram social media account as a forum for eradicating hoaxes. This can develop a two-way communication process that aims to provide false news clarification education. Fake information or news can lead to social conflicts that lead to all layers of the social structure of society and can lead to disintegration of the nation. Their activities in cyberspace also form certain typologies, some are publicists, disseminators, propagandists, hacktivists.